Un/met: a mixed-methods study on primary healthcare needs of the poorest population in Khyber Pakhtunkhwa province, Pakistan - Shaukat, Maira; Imping, Alina; Rogge, Lisa; Khalid, Fatima; Ullah, Safat; Ahmad, Fayaz; Kibria, Zeeshan; Landmann, Andreas; Khan, Zohaib; De Allegri, Manuela (International journal for equity in health, 2024)
Access of all people to the healthcare they need, without financial hardship is the goal of Universal Health Coverage (UHC). As UHC initiatives expand, assessing the needs of vulnerable populations can reveal gaps in the system which may be covered by relevant policies. In this study we (i) identify the met and unmet primary healthcare needs of the poorest population of Khyber Pakhtunkhwa province (KP), Pakistan, and (ii) explore why the gaps exist.